Normative Review Of Regional Tax Legal Political As A Pillar Of Development And People's Welfare In The Region - Nurwahidah Nurwa Al-idris; Muhammad Akbar; Muhammad Gigih Reformasi; Iin Hidayatul Auliya Hidayatul Auliya (Unram Law Review, 2022)
Good and correct local tax management is one indicator of the achievement of regional financial management objectives as mandated by the legislation. Regional taxes, which are one of the sources of regional original income (PAD), have a strategic role in supporting the region's development. This article aims to describe the legal politics of regional tax management and its relation to encouraging development and people's welfare in the regions. This study is a normative study with a statutory approach and conceptual approach. The study result shows that the legal politics of tax is a policy direction for the allocation and use of taxes based on the achievement of the welfare or prosperity of the people. Furthermore, the legal politics of regional tax is an important part of the political management system of regional finance carried out every year containing policies regarding regional development financed by the regional budget. Every regional financial budgeting using local taxes must be directed at the realization of the welfare and prosperity of the people